Improved Performance on Inverted V Eccentrically Braced Frames (EBF) by Implementing Shear Link and Installing Web Stiffener in Link - Hasibuan, Purwandy; Putra, Rudiansyah; Afifuddin, Mochammad; Bermansyah, Surya; Hasan, Muttaqin; Fauzi, Muhammad; Haiqal, Muhammad; Imran, Muhammad; Hanafi, Muhammad Fujii; Shimizu, Masaru; Panjaitan*, Arief (Graduate School of Universitas Syiah Kuala, 2025)
Eccentrically Braced Frame (EBF) is a structural system that is advised to be built in seismically active areas since they are characterized by good stiffness and ductility. A large and stable hysteretic curve, which corresponds to good seismic performance, is produced by the combination of improved stiffness and ductility in EBF. The diagonal component of EBF, known as a brace, contributes to its stiffness. Meanwhile, the short beam, also known as the link element, provides ductility in EBF. One element that is essential as an energy dissipator in EBF is a link element. By displaying a sizable and steady hysteretic curve, a prior study found that EBF with a flexural link could effectively dissipate the seismic energy. But to achieve a higher EBF, the seismic performance still needs to be enhanced. An analysis of various EBF models in Inverted V configurations was conducted in this paper. Each model was prepared with different shear link characteristics. Installing web stiffeners in the link to improve its seismic performance was also taken into consideration in this study. To obtain seismic performance, the cyclic loads were employed to each model under conditions of yield displacement control. Analysis of the data resulted in the load-displacement hysteretic curve. Next, using the hysteretic curve, the three seismic performance parameters, i.e., strength, stiffness, and dissipation energy were further developed. The investigation showed that compared to earlier studies, the EBF with shear links showed a bigger and more stable hysteretic curve which means better dissipated energy. Additionally, adding web stiffeners significantly increases the EBF's seismic capability. Therefore, because of the improved seismic characteristics, it is advised to establish the EBF using a shear link reinforced by web stiffeners in an earthquake-hazard area.